FSG researcher receives Merdeka Award Grant for International Attachment - UiTM, Fakulti Sains Gunaan (Faculty of Applied Sciences, 2019)
Five exceptional young Malaysians received the prestigious Merdeka Award Grant for International Attachment 2019 including a young scientist from FSG UiTM, Dr. Mohd Azri Ab Rani. He will be conducting research on the Sodium Batteries at University of Texas, USA for three months. Among the recipients are Juliana Ooi, Feng Ying Xing, Chrishen Gomez and Dr. Yanny Marliana Baba Ismail. Sultan of Perak and Merdeka Award Royal Patron, His Royal Highness Sultan Nazrin Muizzuddin Shah Ibni Almarhum Sultan Azlan Muhibbuddin Shah AIMaghfur-Lah presented the certificates to the recipients. In his keynote address, Sultan Nazrin said that one of the most rewarding aspects of presenting the grant each year is getting to be part of this next step in the journey of a young Malaysian, in pursuit of his or her aspiration. Congratulations once again to all the recipients!